Advanced passive micro-optical elements - Ruffieux, Patrick (My University, 2008)
Micro-optical elements are optical elements having size or details in the range of the micrometer scale. The emergency of such elements is strongly linked to the development made in the fabrication techniques during the nineties to follow the still actual trend of miniaturization. From this time it has been convenient to separate micro-optical element having refractive or reflective optical design from those ones having strictly diffractive design. In the present thesis we are in between this two fields and from conventional refractive optical elements, different features of physical optics like diffraction, polarization or interference effects are added. We start by adding the birefringent property of liquid crystal polymers (LCP) to microlenses. The interest to employ LCP is linked to the fact that bulky birefringent structures of various shapes can easily be obtained by embossing. Moreover the choice of the optical axis of this material can be chosen by boundary conditions imposed by the different surfaces embedding the liquid crystal. Using this material a micro-optical device allowing the increase of the efficiency of conventional polarizer has been designed, simulated and realized. We continue by studying the influence of the aperture size on the position of the peak irradiance of microlenses. This diffractive effect of the aperture limitation is known as the focal shift which tends to decrease the real focal length obtained from paraxial geometric optics. In the frame of this thesis, we pursue the investigation and show that this effect could be advantageously used to obtain achromatic microlenses. In the frame of beam shaping applications we realized diffusers with very narrow angular distribution. These diffusers allow high energy throughputs and homogeneity distribution for highly coherent sources employed in conventional Fly's eye condensers. The consequences of coherent sources used in such beam shaper are discused in detail and rules are given to employ our diffusers in such systems. To finish, we developed and characterized a new method to fabricate concave microlenses with diffraction limited property and applied them in the realization of optical diffusers.
Thèse de doctorat : Université de Neuchâtel, 2008 ; Th.2023
Keywords: micro-optique; birefringence; cristaux liquides; polariseurs; microlentilles achromatiques; réseaux de microlentilles; homogénéiseur de faisceau; effet de moiré; agrandissement par effet de moiré; afficheurs; diffuseurs; microlentilles concaves; micro-optics; birefringence; liquid cristals; polarizer; achromatic microlenses; microlens arrays; beam homogenizers; moiré; moiré magnifier; displays; diffusers; concave microlenses